Making Sense of Learning A Research-Based Approach - Reid, Norman; Amanat Ali, Asma.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2020)
This textbook brings together findings from global research on teaching and learning, with an emphasis on secondary and higher education. The book is unique in that the content is selected in an original way and its presentation reflects the most recent research evidence related to understanding. The book covers and presents themes that are based tightly on worldwide research evidence, scrupulously avoiding opinion or any dependence on the personal experience of the authors. The book starts by reflecting on educational research itself. The four chapters that follow relate the story of the research that shows how all humans learn and the variations within that framework. These chapters offer a tight framework that underpins much of the rest of the text. The next four chapters look at the way school curricula are organised and how the performance of learners can be assessed. They summarise the research evidence related to thinking skills and consider the importance of practical teaching. This is followed by two chapters that draw from the extensive social psychology research on attitude development as it applies in education, and then by two chapters that summarise the research related to major issues of controversy: the performativity agenda and the issue of quality. One chapter looks at the place of statistics in education. The next two chapters look at the evidence that can support or undermine many typical education beliefs, or myths and mirages. Finally, the last chapter brings it all together and looks into the future, pointing to some areas where future research is likely to be helpful, based on current knowledge.
1 Introduction, The nature of educational research -- 2 How do Students Learn?, The foundations of understanding -- 3 A World of Information, How do our brains handle ideas? -- 4 Why are Concepts Difficult?, Research related to working memory -- 5 Learner Characteristics, What are the key variations in learning? -- 6 Models of the Curriculum, Why do our students study what they study? -- 7 School Subjects and the Curriculum, Why do we teach what we teach? -- 8 Assessment Principles, Moving assessment into a new future -- 9 Assessment Practicalities, How to develop quality assessments -- 10 Thinking Skills, Are there different aspects in thinking? -- 11 Beliefs and Attitudes, Why do attitudes matter? -- 12 The Development of Attitudes, Impact of Attitudes -- 13 Practical Teaching, The Antidote to Boredom -- 14 Intelligence, Ability and Performance, Dangers in past and present thinking -- 15 Developing Quality Education, How do we approach the development of quality? -- 16 Making sense of statistics, How statistics can help us forward in education -- 17 Myths and Mirages, Opinions, Assertion and Evidence -- 18 More Myths and Mirages, Opinions, Assertion and Evidence -- 19 Educational Futures, Key Messages from Research -- Appendices.-.
Keywords: Teaching; Learning; Instruction; Schools; Assessment; Teaching and Teacher Education; Learning & Instruction; Schools and Schooling; Assessment, Testing and Evaluation